2019
DOI: 10.1111/and.13491
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin improves asthenozoospermia by inhibiting reactive oxygen species reproduction through nuclear factor erythroid 2‐related factor 2 activation

Abstract: We conducted this study for the purpose of evaluating the protective mechanisms of curcumin against oxidative stress in asthenozoospermic individuals. Asthenozoospermic individuals were grouped into AS group, curcumin treatment group and brusatol + curcumin treatment group. The sperm motility was measured by computer‐aided sperm analysis. We conducted flow cytometry and spectrophotometry to assess the levels of reactive oxygen species (ROS) and malondialdehyde (MDA). Chlortetracycline (CTC) was used to examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…In light of this, several reports indicated that cryopreservation induced alteration in DNA integrity, lipid peroxidation, ROS, cholesterol content, capacitation [ 34 ], and acrosome reaction in spermatozoa and resulted in failure male fertility potential [ 5 , 7 , 17 ]. However, it has been reported that curcumin has a protective effect on DNA damage, normal development of testicular tissue and avoidance of spermatogenic cell apoptosis [ 12 , 15 , 18 ]. Studies have shown that CU has poor aqueous solubility, poor bioavailability, instability, rapid metabolism, and short half-life [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In light of this, several reports indicated that cryopreservation induced alteration in DNA integrity, lipid peroxidation, ROS, cholesterol content, capacitation [ 34 ], and acrosome reaction in spermatozoa and resulted in failure male fertility potential [ 5 , 7 , 17 ]. However, it has been reported that curcumin has a protective effect on DNA damage, normal development of testicular tissue and avoidance of spermatogenic cell apoptosis [ 12 , 15 , 18 ]. Studies have shown that CU has poor aqueous solubility, poor bioavailability, instability, rapid metabolism, and short half-life [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin is an important natural polyphenolic compound, which has been broadly applied for multimodal uses, such as cosmetic agents, food processing, and in some medical preparations. Curcumin has been reported to be effective in improving sperm mobility in asthenozoospermia patients [ 12 ], owing to its antioxidant capacity, and free radical scavenging [ 12 , 13 ]. Due to its safety, low toxicity and efficacy use in human and animals’ experiments, the US Food and Drug Administration has recommended curcumin as “generally regarded as safe” [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current section, we discuss the impact of naturally occurring compounds on mitochondria to direct the next sections about the special relationship of resveratrol and mitochondria in cancer therapy. Curcumin is one of the most important components of Curcuma longa with excellent therapeutic impacts including anti-tumor [123], hepatoprotective [124], cardioprotective [125], anti-diabetic [126], antioxidant [127] and anti-inflammatory [128]. Newly published articles have shed some light on the ability of curcumin in targeting mitochondria.…”
Section: Regulation Of Mitochondria By Plant-derived Chemicalsmentioning
confidence: 99%
“…Emodin is an anthraquinone derivative with pharmacological effects such as antioxidant, anti-inflammatory, anti-tumor and neuroprotective [127]. Emodin supplementation is suggested to be beneficial in the treatment of colon cancer by regulation of molecular signaling pathways such as MAPK/JNK, PI3K/Akt, NF-κB and STAT to impair MMP, leading to the reduced viability and growth of tumor cells through mitochondrial-dependent manner [132].…”
Section: Regulation Of Mitochondria By Plant-derived Chemicalsmentioning
confidence: 99%